Carbon monoxide catalytic combustion catalyst and preparation method thereof
By crushing, calcining and washing the scrap copper-based methanol catalyst, combined with the modification of aluminate coupling agent and aluminite, an efficient carbon monoxide catalytic combustion catalyst is prepared, solving the complex and costly catalyst preparation The problem has achieved low-cost and efficient catalytic effect.
Patent Information
- Application Number
- CN202411109477.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-13
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-08-13
AI Technical Summary
The catalyst preparation method in the existing carbon monoxide catalytic oxidation purification methods is complex and costly, which leads to limitations in its promotion and application.
The carbon monoxide catalytic combustion catalyst is prepared by using scrap copper-based synthetic methanol catalyst for crushing, calcining, washing, filtration and forming. The carbon monoxide catalytic combustion catalyst is prepared by using copper, zinc and aluminum oxide in the waste catalyst, and alumina is passed through aluminate coupling agent and aluminum trihydrate. Modification improves the activity and water resistance of the catalyst.
It effectively reduces the Na element content in the catalyst, improves the service life and catalytic effect of the catalyst, reduces production costs, realizes low-cost and low-pollution catalyst preparation, and improves the efficiency of carbon monoxide catalytic combustion.
Smart Images

Figure CN119236946A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the fields of air pollution prevention and control, solid waste pollution disposal and the like in advanced environmental protection industries, and in particular to a carbon monoxide catalytic combustion catalyst and a preparation method thereof. Background Art
[0002] Carbon monoxide is an atmospheric pollutant, mainly from the coking and ironmaking processes in the metallurgical industry; the synthetic ammonia and methanol production processes in the chemical industry, etc. Because the affinity of carbon monoxide to hemoglobin is 230 to 270 times greater than the affinity of oxygen to hemoglobin, and the dissociation rate of carboxyhemoglobin formed by carbon monoxide and hemoglobin is 3,600 times slower than that of oxyhemoglobin, animals inhaling carbon monoxide will cause hypoxic poisoning. Long-term exposure to low concentrations of carbon monoxide can cause chronic poisoning, affecting the cardiovascular, cerebrovascular and nervous systems.
[0003] In 2018, the Ministry of Ecology and Environment pointed out in the "Reply to Suggestion No. 7559 of the First Session of the 13th National People's Congress" that "carbon monoxide is one of the six basic controlled pollutants in my country's "Ambient Air Quality Standards". Its emission sources are wide-ranging. Almost all combustion devices will produce carbon monoxide, including boilers, heating furnaces, sintering furnaces, coke ovens, etc. The concentration of carbon monoxide in the regional ambient air is closely related to the number and scale of combustion devices, the combustion efficiency of combustion devices, and the emission rate of high-concentration carbon monoxide gas." The reply also stated that "for areas with excessive carbon monoxide and major emission links, we will work with key provinces to study the necessity of adding carbon monoxide control indicators and related limit values." For the coking industry, the carbon monoxide content in the commonly used exhaust gas from dry coke quenching is about 2-5%. Controlling the amount of air entering the dry quenching furnace is an important means to reduce the amount of carbon monoxide produced in the dry coke quenching flue gas, but at this stage its reduction is limited.
[0004] The main CO purification technologies include physical methods (low temperature separation, adsorption, etc.) and chemical methods (solution absorption, combustion, catalytic oxidation, etc.). Among these technologies, catalytic oxidation is highly favored due to its high purification efficiency, easy operation, and recoverable heat energy. Catalysts are the key core of this technology.
[0005] In the process of realizing the present invention, the applicant discovered that the catalyst preparation method of the existing CO catalytic oxidation purification method is complicated and costly, which greatly limits the promotion and application of the CO catalytic oxidation purification method. Summary of the invention
[0006] 1. Technical issues to be solved
[0007] The present invention is expected to at least partially solve one of the above technical problems.
[0008] 2. Technical Solution
[0009] The first aspect of the present invention provides a method for preparing a carbon monoxide catalytic combustion catalyst. The method for preparing a carbon monoxide catalytic combustion catalyst comprises:
[0010] Step A, crushing the waste copper-based methanol synthesis catalyst to obtain a first powder;
[0011] Step B, calcining the first powder;
[0012] Step C, washing and filtering the first powder after calcination to obtain a filter cake material;
[0013] Step D, drying the filter cake material and then crushing it to obtain a second powder;
[0014] Step E, adding the second powder to the molding aid and kneading to obtain a semi-finished product material;
[0015] Step F, forming the semi-finished product material, and obtaining a carbon monoxide catalytic combustion catalyst after drying and calcining.
[0016] In some embodiments of the present invention, in step A, the waste copper-based methanol synthesis catalyst is used as a reference per unit mass, and in the waste copper-based methanol synthesis catalyst: CuO, its weight percentage content is not less than 50%; Al2O3, its weight percentage content is not less than 10%; ZnO, its weight percentage content is not less than 10%.
[0017] In some embodiments of the present invention, in step B, the first powder is calcined at a temperature between 300 and 450° C., for a time between 3 and 5 hours, in an oxygen-containing atmosphere with an oxygen content of ≥10%.
[0018] In some embodiments of the present invention, in step A, the waste copper-based synthetic methanol catalyst is crushed to a particle size of less than 50 μm; in step C, the first powder after calcination is repeatedly washed and filtered until: the weight percentage content of the Na element is less than 0.08%; the weight percentage content of the Cl element is less than 0.05%; the weight percentage content of the S element is less than 0.05%.
[0019] In some embodiments of the present invention, step E includes: sub-step E1, kneading the second powder with a surfactant, wherein the surfactant includes: an aluminate coupling agent and petroleum ether; sub-step E3, adding a molding aid and continuing to knead.
[0020] In some embodiments of the present invention, step E1 includes: dissolving and dispersing the aluminate coupling agent in petroleum ether to obtain an aluminate coupling agent dispersion; adding the second powder and the aluminate coupling agent dispersion into a kneader for kneading; or, adding the second powder and the aluminate coupling agent into a kneader for solid-solid kneading; adding petroleum ether into the kneader and continuing to knead.
[0021] In some embodiments of the present invention, in the surfactant of sub-step E1, the aluminate coupling agent is isopropyl distearoyloxyaluminate, and its weight percentage content is between 0.1 and 2%, preferably between 0.3 and 1%; the mass of petroleum ether is 5 to 20 times the mass of the aluminate coupling agent, preferably 8 to 15 times.
[0022] In some embodiments of the present invention, between sub-steps E1 and E3, there is also included: sub-step E2, adding a bridging agent and continuing to knead, wherein the bridging agent is gibbsite material, and the weight percentage content of gibbsite is between 2% and 10%, preferably between 3% and 6%.
[0023] In some embodiments of the present invention, in sub-step E3, the molding aid includes: PEO and ammonium bicarbonate, wherein the weight percentage of PEO is between 0.5% and 3%, preferably between 1% and 3%; the weight percentage of ammonium bicarbonate is between 0.5% and 3%, preferably between 0.5% and 2%;
[0024] In some embodiments of the present invention, the molding aid further includes one or more of the following materials: stearic acid, CMC-NH4, monoethanolamine, and ammonia water.
[0025] In some embodiments of the present invention, step D includes: sub-step D1, drying the filter cake material at a drying temperature between 100°C and 300°C; sub-step D2, crushing the dried filter cake material to a particle size less than 50 μm.
[0026] In some embodiments of the present invention, step F includes: sub-step F1, molding the semi-finished material, and the molding process is one of the following: extrusion molding, ball molding, honeycomb extrusion molding, coating molding; sub-step F2, drying the molded material to make the water content less than 5%; sub-step F3, roasting the dried material, and the roasting temperature is between 300 and 500°C.
[0027] The second aspect of the present invention provides a carbon monoxide catalytic combustion catalyst. The carbon monoxide catalytic combustion catalyst is prepared by the above preparation method.
[0028] 3. Beneficial Effects
[0029] It can be seen from the above technical solution that the present invention has at least one of the following beneficial effects compared with the prior art:
[0030] 1. The present invention turns waste into treasure, utilizes waste methanol synthesis catalyst to obtain carbon monoxide catalytic combustion catalyst, and has good prospects for promotion and application.
[0031] In the present invention, the role of a large amount of copper and zinc elements in the waste synthetic methanol catalyst in isolating copper is fully utilized to produce a large number of active sites to compensate for the lack of water resistance of the carbon monoxide catalytic combustion catalyst.
[0032] In the present invention, zinc oxide existing in the waste synthetic methanol catalyst and the -Cu-O-Zn-O-Cu- structure are utilized, and the zinc element is utilized to isolate the copper element, so that the copper oxide is effectively dispersed and the catalytic performance is improved.
[0033] 2. In the present invention, the calcination temperature is 300-450°C, preferably 380-420°C. The calcination temperature cannot be too low or too high. If it is too low, Cu cannot be oxidized to CuO. If it is too high, CuO will decompose into Cu2O, which will also cause the active components to migrate and aggregate, and grow their grains, reducing the catalytic activity. The calcination time should not be too long, which will also cause the active component grains to grow. The calcination time is 1-6 hours, preferably 1-3 hours.
[0034] 3. In the present invention, the applicant prepared a technical solution of crushing, roasting, and repeatedly washing and filtering the waste copper-based synthetic methanol catalyst, which is specifically embodied in steps A to C. Through the combined action of the above steps, the weight percentage content of the Na element in the waste copper-based synthetic methanol catalyst is successfully reduced to less than 0.1%, thereby increasing the service life of the prepared carbon monoxide catalytic combustion catalyst and improving the catalytic effect.
[0035] 4. In the present invention, the alumina that has been passivated by roasting is reactivated by the aluminate coupling agent, making it easier to connect other substances and to connect itself (alumina and alumina), so that it can play the role of a binder again. Therefore, by adding the aluminate coupling agent, the alumina in the waste methanol synthesis catalyst can be fully utilized to increase the strength after molding. At the same time, the coupling agent can also become a bridge connecting inorganic and organic. In the presence of other organic compounds, the coupling agent also plays a certain dispersing role. Petroleum ether is an auxiliary agent of the aluminate coupling agent, which helps to disperse the aluminate coupling agent.
[0036] 5. In the present invention, gibbsite is added to effectively bridge the alumina modified by the aluminate coupling agent during the roasting process. After roasting, gibbsite is converted into alumina, forming a bridge connecting alumina and alumina, and forming channels and holes. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1The present invention is a flow chart of a method for preparing a catalyst for the catalytic combustion of carbon monoxide.
[0038] Figure 2 for Figure 1 The figure shows a schematic diagram of the kneading process of step E of the method for preparing a catalyst for the catalytic combustion of carbon monoxide.
[0039] Figure 3 It is the molecular formula of the aluminum oxide surface modified by the aluminate coupling agent in the embodiment of the present invention.
[0040] Figure 4 It is the molecular formula of gibbsite.
[0041] Figure 5 It is a bridging mechanism utilizing alumina obtained by roasting gibbsite. DETAILED DESCRIPTION
[0042] The present invention aims to provide a low-cost, low-pollution carbon monoxide catalytic combustion catalyst in view of the problems of excessive carbon monoxide emission in waste gases such as coke oven flue gas and dry coke quenching exhaust gas in the prior art and short catalyst life.
[0043] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific implementation methods and with reference to the accompanying drawings.
[0044] A first aspect of the present invention provides a method for preparing a catalyst for the catalytic combustion of carbon monoxide. Figure 1 Flow chart of the method for preparing a catalyst for the catalytic combustion of carbon monoxide according to an embodiment of the present invention. Figure 1 As shown, the method for preparing the catalyst for catalytic combustion of carbon monoxide in this embodiment includes:
[0045] Step A, crushing the waste copper-based methanol synthesis catalyst to obtain a first powder;
[0046] Step B, calcining the first powder;
[0047] Step C, repeatedly washing and filtering the first powder after calcination to obtain a filter cake material;
[0048] Step D, drying the filter cake material and then crushing it to obtain a second powder;
[0049] Step E, adding the second powder to the molding aid and kneading to obtain a semi-finished product material;
[0050] Step F, forming the semi-finished product material, and obtaining a carbon monoxide catalytic combustion catalyst after drying and calcining.
[0051] In this embodiment, waste is turned into treasure, and a waste methanol synthesis catalyst is used to obtain a carbon monoxide catalytic combustion catalyst, which has a good prospect for promotion and application.
[0052] The following is a detailed description of each step of the method for preparing the catalyst for catalytic combustion of carbon monoxide in this embodiment.
[0053] In the prior art, there is a method for preparing a mercury removal agent using a waste copper-based synthetic methanol catalyst. However, the applicant used the product prepared by this method to conduct a carbon monoxide catalytic combustion experiment, but the catalytic effect and service life were not ideal. After theoretical research and repeated experiments by the applicant, it was found that the Na element played a negative role.
[0054] Specifically, the treated product contains a trace amount of Na element. After analysis by inductively coupled plasma emission spectrometer (ICP-OES), the weight percentage content of Na element is between 0.3% and 0.5% with the waste copper-based synthetic methanol catalyst as a reference per unit mass. As a carbon monoxide catalytic combustion catalyst, when the weight percentage content of Na element exceeds 0.1%, it will seriously affect the service life of the catalyst. The reason is that the Na element in the catalyst mainly exists in the form of soluble salts such as Na2SO4 and NaNO3. During use, water vapor and heat will cause the soluble salts to migrate to the catalyst surface, thereby covering the active center and causing the catalyst to deactivate.
[0055] In view of the above analysis, the applicant prepared a technical solution of crushing, roasting, and repeated washing and filtering of waste copper-based synthetic methanol catalyst, which is specifically embodied in steps A to C. Through the combined action of the above steps, the weight percentage content of the Na element in the waste copper-based synthetic methanol catalyst was successfully reduced to less than 0.1%, thereby increasing the service life of the prepared carbon monoxide catalytic combustion catalyst and improving the catalytic effect.
[0056] In the present invention, the applicant has conducted experiments on waste copper-based methanol synthesis catalysts from various sources and found that any waste copper-based methanol synthesis catalyst that meets the following conditions can achieve the present invention: CuO, its weight percentage content is not less than 50%; Al2O3, its weight percentage content is not less than 10%; ZnO, its weight percentage content is not less than 10%. It should be noted again that the weight percentage content in the present invention is based on the waste copper-based methanol synthesis catalyst as a unit mass, which will not be repeated later.
[0057] In order to ensure the rigor of the experimental results, after verifying the waste copper-based methanol synthesis catalysts from various sources, the subsequent experiments were conducted using the same waste copper-based methanol synthesis catalyst. The weight percentage content of the waste copper-based methanol synthesis catalyst is as follows: CuO, 62.63%; ZnO, 21.53%; Al2O3, 12.35%; Fe2O3, 1.84%; SiO2, 0.80%; Na2O, 0.57%; SO2, 0.28%.
[0058] In step A of this embodiment, the waste synthetic methanol catalyst is crushed to a particle size of less than 50 μm to obtain a first powder.
[0059] In the prior art, most synthetic methanol catalysts are formed by tableting, and the shape is a cylinder with a diameter and height of 4 to 5 mm, with high strength and large particles. The waste synthetic methanol catalyst is crushed to facilitate subsequent roasting and water washing. If it is not crushed, the inside of the catalyst will not be exposed to oxygen during roasting, resulting in incomplete roasting; and during the water washing process, water cannot effectively penetrate into the inside of the catalyst and cannot dissolve the impurities inside the catalyst, and the content of Na in the material cannot be effectively reduced, affecting the water washing effect.
[0060] In step B of this embodiment, the first powder is calcined at 300-450° C. for 3-5 hours and then cooled to room temperature. The atmosphere is an oxygen-containing atmosphere with an oxygen content of ≥10%, preferably ≥15%.
[0061] As mentioned above, waste copper-based methanol synthesis catalyst contains more Cu, ZnO, Al2O3 and a small amount of CuO, CuS, Cu2S, ZnS, Fe 3+ , Cl- and other substances, in addition, it also contains trace amounts of Na elements.
[0062] In this step, the purpose of roasting is:
[0063] ①Convert Cu into CuO, so that CuO has carbon monoxide catalytic combustion activity. The calcination temperature is 300-450°C, preferably 380-420°C. The calcination temperature cannot be too low or too high. If it is too low, Cu cannot be oxidized into CuO. If the temperature is too high, CuO will decompose into Cu2O, which will also cause the active components to migrate and aggregate, and cause their grains to grow, reducing the catalytic activity. The calcination time should not be too long, as it will also cause the active component grains to grow. The calcination time is 1-6 hours, preferably 1-3 hours.
[0064] ②Convert sulfur in sulfide into SO2 or SO4 2- SO2 escapes during the roasting process, SO4 2- Remove by subsequent washing.
[0065] In step C of this embodiment, the first powder after calcination is repeatedly washed and filtered until the weight percentage of the Na element is less than 0.08%; the weight percentage of the Cl element is less than 0.05%; and the weight percentage of the S element is less than 0.05%. It should be noted that the weight percentage of the above elements is measured by the ICP method, and the weight percentage is referenced to the waste copper-based synthetic methanol catalyst as the unit mass.
[0066] It should be noted that in the waste copper-based methanol synthesis catalyst, soluble salts such as Na + , Cl - 、SO4 2- These impurities will reduce the life of the catalyst and even reduce its activity. The present invention effectively removes impurities such as Na + , Cl - 、SO4 2- The catalyst life and activity are reduced due to the presence of these substances. At the same time, Cu is converted into CuO by calcination, which improves the catalytic activity.
[0067] Step D of this embodiment includes two steps: a drying step and a crushing step.
[0068] For the drying step, after washing and filtering, the filter cake is dried at a temperature of 100 to 300°C. Considering the energy consumption, it is preferably 150 to 250°C to facilitate subsequent crushing and avoid premature hydrolysis of the aluminate coupling agent before it is fully dispersed. The material with too high water content cannot be crushed to 15 μm. In addition, if an aluminate coupling agent is added later, the water content should be controlled below 1%, preferably below 0.5%.
[0069] As for the crushing step, the material will inevitably clump after washing and drying and must be crushed. Otherwise, when the molding additives are subsequently mixed, the additives will be mixed unevenly. In addition, if the material particles are too large, subsequent material molding operations such as extrusion into strips and honeycomb molding will not be possible.
[0070] In the prior art, there is a carbon monoxide removal catalyst and a preparation method thereof. The catalyst comprises a carrier and an active component supported on the carrier, and the content of the carrier is 30-50% by weight. The carrier is a composite of titanium dioxide and activated alumina, but the addition of titanium dioxide increases the cost on the one hand and reduces the activity of Cu in the catalyst on the other hand.
[0071] In order to solve the problems existing in the prior art, the present invention proposes to use the aluminum oxide and zinc oxide in the waste copper-based methanol synthesis catalyst as carriers, and use the modified aluminum oxide as the main binder for molding. The details are as follows.
[0072] Figure 2 for Figure 1 The kneading process diagram of step E of the method for preparing a carbon monoxide catalytic combustion catalyst is shown in FIG. Figure 2 As shown, in this embodiment, step E includes:
[0073] Sub-step E1, kneading the second powder with a surfactant, wherein the surfactant comprises: an aluminate coupling agent and petroleum ether;
[0074] Sub-step E2, adding a bridging agent and continuing to knead, wherein the bridging agent is gibbsite material;
[0075] Sub-step E3, adding molding aids and continuing kneading.
[0076] It should be noted that the material addition ratios mentioned in the following steps are all ratios without taking water into account.
[0077] In this embodiment, a surfactant including an aluminate coupling agent and petroleum ether is used. Figure 2 As shown, sub-step E1 further includes:
[0078] ① Dissolve the aluminate coupling agent in petroleum ether to obtain an aluminate coupling agent dispersion for standby use; the aluminate addition ratio is 0.1-2%, preferably 0.3-1%; the petroleum ether is 5-20 times the amount of aluminate, preferably 8-15 times;
[0079] ② Add the second powder after the waste methanol catalyst treatment and the above-mentioned aluminate coupling agent dispersion into the kneader and mix for 20 to 40 minutes.
[0080] The functions of the various components of the surfactant added in this sub-step are further described in detail below.
[0081] 1. Aluminate coupling agent
[0082] Aluminate coupling agent is a surfactant that can assist the alumina in the waste catalyst and the added gibbsite to bond other materials, and also transform into alumina after roasting. Since the waste synthetic methanol catalyst contains about 10% (5-15%) alumina, adding aluminate coupling agent can modify the surface of alumina and allow the surface of alumina to be re-grafted with hydroxyl groups (-OH). Figure 3 is the molecular formula of the aluminum oxide surface modified by the aluminate coupling agent in the embodiment of the present invention. Figure 3 As shown, the alumina that has been passivated by roasting is reactivated by the aluminate coupling agent, making it easier to connect to other substances and to connect itself (alumina to alumina), so that it can play the role of a binder again. Therefore, the addition of the aluminate coupling agent can make full use of the alumina in the waste methanol synthesis catalyst and increase the strength after molding. At the same time, the coupling agent can also become a bridge connecting inorganic and organic. In the presence of other organic compounds, the coupling agent also plays a certain dispersing role. However, the amount of aluminate coupling agent added should not be too much, as too much will seriously cover the active center. Aluminate coupling agents have several models according to different organic groups, but the models written by various manufacturers are not uniform.
[0083] In this embodiment, the coupling agent component used is isopropyl distearyloxyaluminate, which is confirmed to achieve the corresponding function. According to the general understanding of those skilled in the art, other types of coupling agents should also be able to achieve similar functions.
[0084] 2. Petroleum ether
[0085] Petroleum ether is an auxiliary agent of aluminate coupling agent, which helps to disperse the aluminate coupling agent. Because aluminate coupling agent will hydrolyze when it meets water, if it is hydrolyzed before it is effectively dispersed, the aluminate coupling agent cannot play its role. Therefore, the aluminate coupling agent must be dispersed on the surface of the alumina to be modified first, and then hydrolyzed, in order to fully play the role of the aluminate coupling agent. As mentioned above, aluminate coupling agent will hydrolyze when it meets water, and it can only be effectively dispersed by adding a solvent to dissolve it or raising the temperature (above 80°C) to melt it. If the aluminate coupling agent is dispersed by melting at a high temperature, petroleum ether can be omitted. The added petroleum ether evaporates and forms pores during the drying process.
[0086] In addition, it should be noted that the above is only one implementation of the present invention. In another implementation of the present invention, it can also be: adding the second powder and the aluminate coupling agent to a kneader for solid-solid mixing; adding petroleum ether to the kneader and continuing to knead. Or: first dissolve the aluminate coupling agent in petroleum ether and disperse it, and configure it into an aluminate coupling agent petroleum ether dispersion for standby use, place the second powder in step D in a kneader, and start stirring, then slowly pour the aluminate coupling agent petroleum ether dispersion into the kneader, and knead for 20 to 40 minutes. These two methods can also achieve similar effects.
[0087] In this embodiment, Figure 2 As shown, in sub-step E2, gibbsite is added to a kneader and kneaded for 20 to 30 minutes. The mass ratio of gibbsite added is 2 to 10%, preferably 3 to 6%.
[0088] In the prior art, there is no technical solution for modifying alumina using an aluminate coupling agent and simultaneously using gibbsite for bridging. Figure 4 It is the molecular formula of gibbsite. Figure 5 This is a bridging mechanism of alumina obtained by roasting gibbsite. Figure 4 and Figure 5 As shown, the addition of gibbsite can effectively bridge the alumina modified by the aluminate coupling agent during the roasting process. After roasting, gibbsite will be transformed into alumina, forming a bridge connecting alumina and alumina, and forming channels and holes.
[0089] In this embodiment, in sub-step E3, the molding aid includes: PEO ((polyethylene oxide)), ammonium bicarbonate. Sub-step E3 further includes:
[0090] ① Add PEO and knead for 20 to 30 minutes. The proportion of PEO added is 0.5 to 3%, preferably 1 to 3%;
[0091] ② Add 20g of water, knead for 10 minutes, then add 20g of water, knead for 10-20 minutes to hydrolyze the aluminate coupling agent;
[0092] ③ Add ammonium bicarbonate and knead for 10 to 20 minutes. The proportion of ammonium bicarbonate added is 0.5 to 3%, preferably 0.5 to 2%;
[0093] ④Add the remaining water in small amounts and multiple times. To meet the requirements of extrusion molding, the amount added can be appropriately increased or decreased according to the conditions.
[0094] Those skilled in the art should understand that the above are only the molding aids required for extrusion molding. In other embodiments of the present invention, if other molding methods are required, corresponding molding aids can be selected, such as one or more of stearic acid, ammonium bicarbonate, PEO, CMC-NH4 (ammonium carboxymethyl cellulose), monoethanolamine, and ammonia water. Depending on different molding processes, the added molding aids will be different.
[0095] The functions of the various components of the molding aids added in this sub-step are further described in detail below.
[0096] 1. Stearic acid
[0097] Stearic acid mainly plays a lubricating role during the extrusion process;
[0098] 2. Ammonium bicarbonate
[0099] Ammonium bicarbonate is a pH regulator that can neutralize the weak acid produced by the hydrolysis of the aluminate coupling agent. It is also a pore-forming agent and can be completely decomposed at temperatures above 60°C.
[0100] 3. PEO and CMC-NH4
[0101] PEO, CMC-NH4 and monoethanolamine mainly play a bonding role, which is convenient for extrusion molding. They are almost completely burned out during roasting, and at the same time, pores are formed;
[0102] 4. Ammonia
[0103] Ammonia water mainly plays the role of assisting the dissolution of CMC-NH4.
[0104] In step F of this embodiment, the semi-finished product material is formed, dried and calcined to obtain a carbon monoxide catalytic combustion catalyst. This step F further includes:
[0105] Sub-step F1, molding the semi-finished product material, the molding process is one of the following: extrusion molding, ball rolling molding, honeycomb extrusion molding, coating molding;
[0106] Sub-step F2, drying the formed material to reduce the water content to less than 5%, preferably to less than 3% (the maximum water content for extrusion molding can be controlled to less than 5%);
[0107] Sub-step F3, calcining the dried material at a temperature of 300-500°C, preferably 350-400°C.
[0108] Those skilled in the art should understand that various molding processes are also partially based on previous industry experience, such as extrusion molding, ball molding, honeycomb extrusion molding, etc., but they will vary for different materials and different operating conditions.
[0109] It should also be noted that some prior art carbon monoxide removal catalysts use titanium dioxide as the main component, which increases the cost on the one hand and reduces the activity of Cu in the catalyst on the other hand. Some prior art carbon monoxide catalysts also add silicon dioxide. However, the applicant found that the addition of silicon dioxide does not have any benefit on water resistance. On the contrary, the addition of silicon dioxide dilutes the active components and thus reduces the overall performance of the catalyst.
[0110] Different from the above-mentioned prior art, the present invention also has the following characteristics:
[0111] ① No introduction of titanium dioxide
[0112] In the present invention, titanium dioxide is not introduced, thus avoiding the influence of the activity of copper due to the introduction of titanium dioxide. The present invention mainly utilizes the aluminum oxide and zinc oxide in the waste synthetic methanol catalyst as carriers, and utilizes the aluminum oxide itself as the main binder for molding.
[0113] ② No introduction of silica
[0114] In the present invention, no substances such as silicon dioxide which do not contribute to the catalytic activity are added. Instead, the role of a large amount of copper and zinc elements in the waste synthetic methanol catalyst to isolate copper is fully utilized to produce a large number of active sites, so as to make up for the insufficient water resistance of the carbon monoxide catalytic combustion catalyst.
[0115] ③ Use zinc oxide in the waste methanol synthesis catalyst to isolate copper elements
[0116] In addition, by utilizing the zinc oxide existing in the waste synthetic methanol catalyst and the -Cu-O-Zn-O-Cu- structure, the zinc element is used to isolate the copper element, effectively dispersing the copper oxide and improving the catalytic performance.
[0117] ④Use modifiers to improve the strength and effectiveness of carbon monoxide catalytic combustion catalysts
[0118] In the present invention, a small amount of aluminate coupling agent is added to modify the alumina in the waste methanol synthesis catalyst so that hydroxyl groups (-OH) are grafted on its surface, and gibbsite is added to bridge the alumina, which can greatly improve the strength of the catalyst (extrusion molding, the amount of aluminate coupling agent added is 0.5%, the amount of gibbsite added is 5%, and the radial crushing resistance is about 110N / cm).
[0119] The second aspect of the present invention provides a carbon monoxide catalytic combustion catalyst, characterized in that it is prepared by the above-mentioned preparation method. Regarding the preparation method, reference can be made to the description of the previous embodiment, which will not be repeated here.
[0120] The present invention is described in more detail below in combination with comparative examples and experimental examples.
[0121] The CO conversion rate test method described in the embodiments of the present invention and the comparative examples is as follows: 5g of catalyst is loaded into a fixed bed reactor, and a gas containing 2% CO, 20% CO2, 4% O2, 5% H2O, and the rest nitrogen is introduced into the reactor inlet under normal pressure, and the temperature is slowly increased until the bed temperature reaches 120°C and stabilized for 2h, and the outlet CO concentration is recorded, and the conversion rate is calculated by the outlet CO concentration. The conversion rate calculation formula is as follows:
[0122]
[0123] Comparative Example 1:
[0124] Step A', crushing the waste methanol synthesis catalyst into powder with a particle size of less than 75 μm;
[0125] Step B', add 174g of the powder of step A' and 11g of pseudo-boehmite into a kneader, and dry mix for 20 minutes;
[0126] Step C', adding 80 g of water, wet mixing for 20 minutes, and extruding;
[0127] Step D', drying to a water content of less than 5%;
[0128] Step E', calcining at 500°C for 3h to obtain a finished catalyst, referred to as comparative sample 1.
[0129] The test showed that the CO conversion rate of the comparative sample 1 was 35%, and the radial crushing resistance was 60 N / cm.
[0130] Example 1
[0131] Step A, crushing the waste methanol synthesis catalyst to a particle size of less than 30 μm;
[0132] Step B, calcining the powder obtained in step A at 420° C. in an oxygen-containing atmosphere for 3 hours, and cooling to room temperature;
[0133] Step C, repeatedly washing and filtering the calcined powder obtained in step B until the weight percentage of Na element is less than 0.04%, Cl content is less than 0.03%, and S content is less than 0.03%, and collecting the filter cake;
[0134] Step D, drying the filter cake obtained in step C until the water content is less than 1%;
[0135] Step E, crushing the material obtained by drying in step D into pieces smaller than 15 μm, thus obtaining the treated catalyst powder; in the following operations, the amount and proportion of each material added are shown in ingredient table 1.
[0136] Table 1 Ingredients in modified alumina and preparatory steps of forming
[0137]
[0138] Step F, dissolving and dispersing the aluminate coupling agent in petroleum ether to obtain an aluminate coupling agent dispersion;
[0139] Step G, adding the powder obtained in step E and the aluminate coupling agent dispersion into a kneader, and kneading for 40 minutes;
[0140] Step H, adding gibbsite and kneading for 30 minutes;
[0141] Step I, adding PEO and kneading for 30 minutes;
[0142] Step J, first add 20 g of water, mix for 10 minutes, then add 20 g of water, mix for 20 minutes;
[0143] Step K, adding ammonium bicarbonate and kneading for 20 minutes;
[0144] Step L, adding the remaining amount of water in small amounts and multiple times;
[0145] Step M, extruding the material into strips, drying at 120° C. for 3 hours, with a water content of 2.1%;
[0146] Step N, calcining at 370° C. for 3 hours to obtain a carbon monoxide catalytic combustion catalyst, thereby obtaining sample 1.
[0147] The test showed that the CO conversion rate of sample 1 was 100%, and the radial crushing resistance was 110 N / cm.
[0148] Embodiment 2:
[0149] This example is similar to Example 1, except that: ① in step A, the waste methanol synthesis catalyst is crushed to a particle size of less than 50 μm; ② in step B, the powder obtained in step A is placed at 500° C. and calcined in an oxygen-containing atmosphere for 5 hours. Sample 2 is obtained through Example 2.
[0150] The test showed that the CO conversion rate of sample 2 was 98% and the radial crushing resistance was 108 N / cm.
[0151] Embodiment 3:
[0152] This example is similar to Example 1, except that: ① in step C, the calcined powder obtained in step B is repeatedly washed and filtered until the Na content is less than 0.08%, the Cl content is less than 0.05%, and the S content is less than 0.05%; ② in step B, the powder obtained in step A is placed at 500°C and calcined in an oxygen-containing atmosphere for 5 hours. After Example 3, Sample 3 is obtained.
[0153] The test showed that the CO conversion rate of sample 3 was 97% and the radial crushing resistance was 109 N / cm.
[0154] Embodiment 4:
[0155] This example is similar to Example 1, except that in step F and step G, the powder obtained in step E and the coupling agent are directly added to the kneader, kneaded for 20 minutes, and then petroleum ether is added and kneaded for 20 minutes. Sample 4 is obtained through Example 4.
[0156] The test showed that the CO conversion rate of sample 4 was 98%, and the radial crushing resistance was 98 N / cm.
[0157] Embodiment 5:
[0158] This example is similar to Example 1, except that in step F, the amount of aluminate coupling agent used is 2 g, and the amount of petroleum ether used is 24 g. After Example 5, Sample 5 is obtained.
[0159] The test showed that the CO conversion rate of sample 5 was 93% and the radial crushing resistance was 120 N / cm.
[0160] Embodiment 6:
[0161] This example is similar to Example 1, except that in step H, 6 g of gibbsite is added. After Example 6, Sample 6 is obtained.
[0162] The test showed that the CO conversion rate of sample 6 was 100%, and the radial crushing resistance was 85 N / cm.
[0163] At this point, the various embodiments of the present invention have been introduced. According to the above description, those skilled in the art should have a clear understanding of the present invention.
[0164] It should be noted that, unless explicitly indicated to the contrary, the numerical parameters in the specification and claims of the present invention may be approximate values and may be changed according to the content of the present invention. Specifically, all the numbers indicating the content of the composition, reaction conditions, etc. recorded in the specification and claims should be understood to be modified by the term "about" in all cases, and the meaning of the expression is to include a change of ±10% from a specific number in some embodiments.
[0165] The ordinal numbers used in the specification and claims, such as "first", as well as Arabic numerals, letters, etc., to modify the corresponding elements (or steps) are intended only to clearly distinguish an element (or step) with a certain name from another element (or step) with the same name, and do not mean that the element (or step) has any ordinal number, nor do they represent the order of one element (or step) and another element (or step).
[0166] Meanwhile, unless steps are specifically described or must occur in sequence, the order of the steps is not limited to that listed above and may be changed or rearranged according to desired designs.
[0167] Those skilled in the art should understand that in the claims and description of the present invention, the word "comprising" does not exclude the existence of elements (or steps) not listed in the claims. The word "a" or "an" preceding an element (or step) does not exclude the existence of multiple such elements (or steps).
[0168] For certain implementations, if they are not the key content of the present invention and are well known to ordinary technicians in the relevant technical field, they are not described in detail in the drawings or text of the specification due to space limitations. In this case, reference can be made to relevant existing technologies for understanding.
[0169] Furthermore, the above embodiments are provided merely to enable the present invention to satisfy legal requirements, and the present invention may be embodied in many different forms and should not be construed as limited to the embodiments set forth herein.
[0170] Similarly, it should be understood that in order to simplify the present invention, in the above description of the exemplary embodiments of the present invention, the various features of the present invention are sometimes grouped together into a single embodiment, figure, or description thereof. However, the method of the invention should not be interpreted as reflecting the following intention: the claimed invention requires more features than the features explicitly stated in each claim. More specifically, as reflected in the claims, each inventive aspect lies in less than all the features of the previous single embodiment. Moreover, the embodiments can be mixed and matched with each other or with other embodiments based on design and reliability considerations, that is, the technical features in different embodiments can be freely combined to form more embodiments. Therefore, the claims following the specific embodiment are hereby explicitly incorporated into the specific embodiment, wherein each claim itself serves as a separate embodiment of the present invention.
[0171] The above specific embodiments provide a detailed description of the objectives, technical means and beneficial effects of the present invention. It should be understood that the purpose of the detailed description is to enable those skilled in the art to understand the present invention more clearly, and it is not used to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a carbon monoxide catalytic combustion catalyst, characterized in that: include: Step A, crushing the waste copper-based methanol synthesis catalyst to obtain a first powder; Step B, calcining the first powder; Step C, washing and filtering the first powder after calcination to obtain a filter cake material; Step D, drying the filter cake material and then crushing it to obtain a second powder; Step E, adding the second powder to the molding aid and kneading to obtain a semi-finished product material; Step F, forming the semi-finished product material, and obtaining a carbon monoxide catalytic combustion catalyst after drying and calcining.
2. The preparation method according to claim 1, characterized in that: In the step A, the waste copper-based methanol synthesis catalyst is used as a unit mass for reference, and the waste copper-based methanol synthesis catalyst includes: CuO, the weight percentage of which is not less than 50%; Al2O3, the weight percentage of which is not less than 10%; ZnO, its weight percentage content is not less than 10%.
3. The preparation method according to claim 1, characterized in that: In the step B, the first powder is calcined at a temperature between 300° C. and 450° C. for a time between 3 and 5 hours in an oxygen-containing atmosphere with an oxygen content of ≥10%.
4. The preparation method according to claim 2, characterized in that: In the step A, the waste copper-based methanol synthesis catalyst is crushed to a particle size of less than 50 μm; In the step C, the first powder after calcination is repeatedly washed and filtered until: The weight percentage content of Na element is less than 0.08%; The weight percentage content of Cl element is less than 0.05%; The weight percentage content of S element is less than 0.05%.
5. The preparation method according to claim 1, characterized in that: The step E comprises: Sub-step E1, kneading the second powder with a surfactant, wherein the surfactant comprises: an aluminate coupling agent and petroleum ether; Sub-step E3, adding molding aids and continuing kneading.
6. The preparation method according to claim 5, characterized in that: The step E1 comprises: dissolving and dispersing the aluminate coupling agent in petroleum ether to obtain an aluminate coupling agent dispersion; adding the second powder and the aluminate coupling agent dispersion into a kneader for kneading; or, adding the second powder and the aluminate coupling agent into a kneader for solid-solid kneading; adding petroleum ether into the kneader and continuing kneading; And / or, in the surfactant of sub-step E1, the aluminate coupling agent is isopropyl distearoyloxyaluminate, and its weight percentage content is between 0.1 and 2%, preferably between 0.3 and 1%; the mass of the petroleum ether is 5 to 20 times the mass of the aluminate coupling agent, preferably 8 to 15 times.
7. The preparation method according to claim 5, characterized in that: The sub-steps E1 and E3 also include: Sub-step E2, adding a bridging agent and continuing kneading, wherein the bridging agent is gibbsite material, and the weight percentage content of the gibbsite is between 2% and 10%, preferably between 3% and 6%.
8. The preparation method according to claim 5, characterized in that: In the sub-step E3, the molding aid includes: PEO and ammonium bicarbonate, wherein the weight percentage of the PEO is between 0.5% and 3%, preferably between 1% and 3%; the weight percentage of the ammonium bicarbonate is between 0.5% and 3%, preferably between 0.5% and 2%; And / or, the molding aid further includes one or more of the following materials: stearic acid, CMC-NH4, monoethanolamine, and ammonia water.
9. The preparation method according to claim 1, characterized in that: The step D comprises: Sub-step D1, drying the filter cake material at a drying temperature between 100° C. and 300° C.; Sub-step D2, crushing the dried filter cake material to a particle size less than 50 μm; And / or, step F comprises: Sub-step F1, molding the semi-finished product material, the molding process is one of the following: extrusion molding, ball molding, honeycomb extrusion molding, coating molding; Sub-step F2, drying the formed material to reduce the moisture content to less than 5%; Sub-step F3, calcining the dried material at a temperature of 300-500°C.
10. A carbon monoxide catalytic combustion catalyst, characterized in that: Prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Water-resistant palladium-based catalyst for catalytically combusting benzene as well as preparation method and application of water-resistant palladium-based catalyst
CN108273500A
Protective agent for methanol synthesis catalyst and preparation method and application of protective agent
CN108854476A
Treatment method of waste catalyst, HZSM-5 molecular sieve and preparation method and application of HZSM-5 molecular sieve
CN112093809A
Method and catalyst for removing carbon monoxide
JP2001212432A
Method of preparing catalyst for methanol synthesis and carbon monooxide conversion
RU2500470C1
